2012
DOI: 10.17221/80/2011-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of adaptive cluster sampling and traditional sampling for coastal mangrove in Hainan of China

Abstract: Based on two species of Coastal Mangrove in Hainan of China, Sonneratia Apetala Buch-Ham and Sonneratia caseoli, we estimated the density of the two species to evaluate the efficiency of adaptive cluster sampling (ACS), simple random sampling (SRS) and traditional systematic sampling (SYS). Our initial experimental designs for ACS consisted of 5 unit areas, 6 initial sampling proportions, 4 initial sample sizes and 5 criterion values in 1,000 repetitions. From the aspect of factors influencing efficiency, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…However, Prodan's points and Strand's lines have showed operationally impracticable, due to the area size and the difficulty to include trees of rare species in the sampling units. Thus, the results confirm the second hypothesis, that the adaptive cluster sampling reduces the zeroplots to estimate the commercial volume (Table II), and is a quite appropriated procedure for sampling rare populations of many kinds (Thompson 1990, Roesch Jr 1993, Brown 2003, Talvitie et al 2006, Soares et al 2009, Lei et al 2012.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, Prodan's points and Strand's lines have showed operationally impracticable, due to the area size and the difficulty to include trees of rare species in the sampling units. Thus, the results confirm the second hypothesis, that the adaptive cluster sampling reduces the zeroplots to estimate the commercial volume (Table II), and is a quite appropriated procedure for sampling rare populations of many kinds (Thompson 1990, Roesch Jr 1993, Brown 2003, Talvitie et al 2006, Soares et al 2009, Lei et al 2012.…”
Section: Discussionsupporting
confidence: 72%
“…When applying adaptive cluster sampling, Talvitie et al (2006) and Lei et al (2012) observed that this procedure results in higher efficiency, when compared to conventional sampling procedures, highlighting its importance for surveying rare and aggregate populations. However, few studies have considered the problems of forest sampling with adaptive clusters (Roesch Jr 1993, Acharya et al 2000, since the sub-sampling of rare species results in a considerable underestimation of the biodiversity (Hopkins 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a two-stage cluster (probability) sampling technique (Thompson, 2012, p. 254), the data were collected from 127 respondents in the C&T sector (Lei, Shi, & Zhao, 2012). The C&T sector was divided into various divisions ranging from clothing retailers to manufacturers, and the second stage involved a selection of company representatives from the identified clusters.…”
Section: Methodsmentioning
confidence: 99%
“…The instruments were developed primarily on the basis of the literature on competitive strategy and tested in in among a sample of stakeholders in the clothing and textile industry in Zimbabwe. Using a two-stage cluster (probability) sampling technique (Thompson, 2012) data was collected from 127 respondents in the clothing and textile sector (Lei et al, 2012). The clothing and textile sector was divided into various sectors ranging from clothing retailers to manufacturers, and the second stage involved a selection of company representatives from the identified clusters.…”
Section: Methodsmentioning
confidence: 99%